Urinary Biomarkers for Phthalates Associated with Asthma in Norwegian Children - Bertelsen, Randi J. (National Institute of Environmental Health Sciences, 2012)
Background: High-molecular-weight phthalates in indoor dust have been associated with asthma in children, but few studies have evaluated phthalate biomarkers in association with respiratory outcomes. Objectives: We explored the association between urinary concentrations of phthalate metabolites and current asthma. Methods: In a cross-sectional analysis, 11 metabolites of 8 phthalates [including four metabolites of di(2-ethylhexyl) phthalate] were measured in one first morning void collected from 2001 through 2004 from 623 10-year-old Norwegian children. Logistic regression models controlling for urine specific gravity, sex, parental asthma, and income were used to estimate associations between current asthma and phthalate metabolite concentrations by quartiles or as log(10)-transformed variables. Results: Current asthma was associated with both mono(carboxyoctyl) phthalate (MCOP) and mono(carboxynonyl) phthalate (MCNP), although the association was limited to those in the highest quartile of these chemicals. The adjusted odds ratio (aOR) for current asthma was 1.9 (95% CI: 1.0, 3.3) for the highest MCOP quartile compared with the lowest quartile, and 1.3 (95% CI: 0.98, 1.7) for an interquartile-range increase. The aOR for current asthma was 2.2 (95% CI: 1.2, 4.0) for the highest MCNP quartile and 1.3 (95% CI: 1.0, 1.7) for an interquartile-range increase. The other phthalate metabolites were not associated with current asthma. Conclusions: Current asthma was associated with the highest quartiles of MCOP and MCNP, metabolites of two high molecular weight phthalates, diisononyl phthalate and diisodecyl phthalate, respectively. Given the short biological half-life of the phthalates and the cross-sectional design, our findings should be interpreted cautiously.